An Auroral Alfvén Wave Cascade - Chaston, C. C. (Frontiers in Astronomy and Space Sciences, 2021)
Folding, kinking, curling and vortical optical forms are distinctive features of most bright auroral displays. These forms are symptomatic of non-linear forcing of the plasma above auroral arcs resulting from the intensification of electrical currents and Alfvén waves along high-latitude geomagnetic field-lines during periods of disturbed space weather. Electrons accelerated to energies sufficient to carry these currents impact the atmosphere and drive visible emission with spatial structure and dynamics that replicate the morphology and time evolution of the plasma region where the acceleration occurs. Movies of active auroral displays, particularly when combined with conjugate in-situ fields and plasma measurements, therefore capture the physics of a driven, non-linearly evolving space plasma system. Here a perspective emphasizing the utility of combining in-situ measurements through the auroral acceleration region with high time and spatial resolution auroral imaging for the study of space plasma turbulence is presented. It is demonstrated how this special capacity reveals the operation of a cascade of vortical flows and currents through the auroral acceleration region regulated by the physics Alfvén waves similar to that thought to operate in the Solar wind.